Locating Suburbia Memory, Place, Creativity - Hamilton, Paula (UTS ePRESS, 2013)
The identity of suburbia, so far as it can be ascribed one, is shifting and insecure, a borderline and liminal space. Dominant stereotypes have listed it as 'on the margins' beyond edges of cultural sophistication and tradition' and the areas that make up 'sprawl'. But in the twenty-first century this static view has to be modified. As is evident from this collection, suburban dwellers themselves have redefined themselves. This collection explores the range and complexity of twenty-first century responses to city suburbs, predominantly in Sydney. It draws on a range of approaches - from history to creative non-fiction and multi-media.